E-Module Needs Analysis Studyfor Bumdes Staff to Improve Bumdes Management Capabilities Integrated With The Village Information System (SID) - Diny Eriska Khairun Nisa; Djono Djono; Sri Sumaryati (Universitas Sebelas Maret, 2023)
The development of information technology requires the process of digitiza-tion in all aspects, and the means commonly used to convey information need to be directed to digital and control activities that are starting to lead to digitalization. Therefore, this study aims to analyze the needs of BUMDes managers to manage BUMDes activities that are integrated with the village information system (SID). This research is a qualitative type, with a descrip-tive type, the research subjects who became information consisted of 4 BUMDes managers with non-test data collection techniques accompanied by instruments namely observation sheets and lists of questions. The data analy-sis technique used is descriptive analysis technique. The research results show that the ability possessed by BUMDes management is still quite low and while carrying out management activities it is still fixated on administra-tive matters, not being innovative in formulating a program. Apart from that, the obstacles they face are also because some of the managers are still rela-tively new to the presence of BUMDes so they still cannot fully understand the duties and functions of BUMDes itself, therefore they need media that contains information in electronic module format or e-module on how to manage BUMDes digitally and has been integrated with an information sys-tem, so that managers can be better prepared and understand howBUMDes works. This research will have an impact on improving the quality of human resources, from independent learning through e-modules whose needs are being analyzed, a product will be created for BUMDes employees that they can learn from.